4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Identification of conserved vaccine targets in Mycoplasma bovis through integrated pan-genome and reverse vaccinology approaches with in vivo immunogenicity and safety evaluation - Jiaming Mu; Zhongmei Ma; Jie Li; Xuepeng Cai; Qingling Meng; Jun Qiao (The Veterinary Journal, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)